Comparing material flow control mechanisms using simulation optimization - André, Maria Manuela Lobão Alves (2013)
In this study, discrete event simulation is used for comparing the performance of three material flow control mechanisms: push-MRP, Generic Kanban System (GKS) and generic Paired-cell Overlapping Loops of Cards with Authorization (GPOLCA). The former does not impose restriction to the number of jobs that are released into the supply chain. The latter two are card-based control mechanisms, where the number of jobs in the supply chain is restricted. The simulation models of these mechanisms are developed in Arena® and optimized using OptQuest®. The average total work in process and the average system throughput are used to evaluate the performance of the mechanisms. We found that GKS outperforms GPOLCA and MRP for high levels of throughput.